Investigation of the maternal and cord plasma levels of IL-1 beta, TNF-alpha and VEGF in early membrane rupture - Kucukgul, Sukran; Ozkan, Zehra Sema; Yavuzkir, Seyda; Ilhan, Necip (Taylor & Francis Ltd, 2016)
Objective: Recent studies indicate a relationship between early membrane rupture (EMR) and proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin (IL) and angiogenic factors like vascular endothelial growth factor (VEGF). In this study, we aimed to investigate the relationship between EMR and maternal and cord blood plasma levels of TNF-alpha, IL-1 beta and VEGF. Methods: This prospective, cross-sectional study was conducted with 85 pregnant women. The patients were divided into four groups as Group I (term EMR group, n = 21), Group II (preterm EMR group, n = 23), Group III (preterm non-EMR group, n = 19) and Group IV (term non-EMR group, n = 22). Plasma levels were assayed with ELISA method. Results: IL-1 beta levels were significantly lower, but TNF-alpha levels were significantly higher in maternal and cord plasma of EMR participants compared to non-EMR participants. There was no significant difference for VEGF levels. Cord plasma TNF-alpha levels were significantly higher than maternal plasma levels in EMR participants and cord plasma. VEGF levels were significantly higher than maternal levels in all participants. Conclusions: Higher TNF-alpha levels in our EMR participants indicate an inflammatory process during EMR. Higher cord plasma VEGF levels may point out placental or fetal production. Further studies conducted with expanded populations are needed to discuss our results.
Keywords: Delivery; early membrane rupture; interleukin 1 beta; tumor necrosis factor alpha; vascular endothelial growth factor